Regional CO2 impact assessment of road infrastructure improvements. (January 2021) - Sharifi, Farinoush; Birt, Andrew G.; Gu, Chaoyi; Shelton, Jeff; Farzaneh, Reza; Zietsman, Joe; Fraser, Andrew; Chester, Mikhail
Highlights: The framework evaluates the impact of infrastructure improvements on regional CO2 . We estimated the CO2 from traffic, construction, and maintenance. Three roadway modifications were studied: X-ramps, braided ramps and roundabouts. The cost-effectiveness of roundabouts ranges from 30 to 130 per tonne of CO2 . Abstract: Transparent methods of estimating CO2 emissions from transportation sources are necessary to evaluate mitigation strategies. This study proposes a framework to assess the regional impact of roadway designs on CO2 emissions. First, three roadway infrastructure configurations were designed to improve the traffic flow at intersections and interchanges. Second, the economical and environmental life-cycle cost assessments of constructing and maintaining new infrastructures were developed. Then, the effects of infrastructure on regional vehicle CO2 emissions were modeled using a simulation-based dynamic traffic assignment model coupled with the U.S. Environmental Protection Agency's MOtor Vehicle Emission Simulator (MOVES) model. The case study estimated that converting 72 stop signs to roundabouts within El Paso, TX, reduced daily vehicular CO2 emissions by more than 50 tonnes, paying back the CO2 from construction and maintenance within 2.5 to 2.9 years. The roundabout modifications' cost-effectiveness ranged from 30 to 130 per tonne of CO2 over a 30-year assessment.